2021
DOI: 10.3892/etm.2021.9885
|View full text |Cite
|
Sign up to set email alerts
|

Actin-binding protein anillin promotes the progression of hepatocellular carcinoma in vitro and in mice

Abstract: Hepatocellular carcinoma (HCC) is a common type of tumor with high mortality worldwide. Investigations associated with the molecular etiology of HCC and screening novel therapeutic targets are still urgently in need. Anillin (ANLN), as a type of evolutionarily conserved actin-binding protein, is involved in multiple cellular processes. ANLN widely affected the progression and metastasis of several types of cancer, and its overexpression was frequently demonstrated in previous studies. The present study demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…For HCC, consistent with these findings, our previous study has already verified that Anillin was over-expressed in HCC and facilitated both tumor cell proliferation and tumor growth [35]. Similarly, at about the same time, our findings are also matched with some of the other authors' discoveries on the general over-expression of Anillin in HCC and its promoting effects on either tumorigenesis or development [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…For HCC, consistent with these findings, our previous study has already verified that Anillin was over-expressed in HCC and facilitated both tumor cell proliferation and tumor growth [35]. Similarly, at about the same time, our findings are also matched with some of the other authors' discoveries on the general over-expression of Anillin in HCC and its promoting effects on either tumorigenesis or development [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…However, numerous recent studies suggest that anillin is involved in tumorigenesis in various types of cells. For example [ 66 ], demonstrated that anillin is overexpressed in human gastric cancer (GC) tissues and that depletion of anillin in these tissues inhibits the proliferation of GC cells. Additionally, a recent study by Xiao and colleagues (2020) investigated the regulation mechanism of anillin in human hepatocellular carcinoma (HCC).…”
Section: Cytokinesis Anillin and Cancermentioning
confidence: 99%
“…In future, SIM-TIRF technology will be extended to the imaging of biological tissues with more complex structures and morphologies, such as macromolecular yeast nuclear-pore complexes [165,166]. Although theoretical research on the yeast nuclear-pore complex has reached an advanced stage, experimental verification remains challenging [167][168][169]. Another meaningful research area in the future is the SIM-cTIRF.…”
Section: Summary and Prospectsmentioning
confidence: 99%